PENGARUH BRAND IMAGE, PRODUK, PELAYANAN DAN PROMOSI TERHADAP KEPUASAN NASABAH PT. BANK NEGARA INDONESIA (PERSERO) Tbk KCP BAYUNG LENCIR - Adi Marzuki; Luis Marnisah; Siti Komariah Hildayanti (Program Magister Manajemen Indo Global Mandiri University, 2021)
Currently, more and more banking companies are competing for control of the existing market share by creating customer satisfaction. Customer satisfaction is the main thing for banks to gain the trust of customers to continue using their services. In this study, there are five variables used, namely Brand Image (X1), Product (X2), Service (X3), Promotion (X4) and Customer Satisfaction (Y). The type of research used in this research is descriptive verification method with a quantitative approach. Data collection is obtained through distributing questionnaires to customers of PT. Bank Negara Indonesia (Persero) Tbk KCP Bayung Lencir which is still active. The sample used in this study amounted to 261 respondents. The sampling technique used was purposive sampling with data analysis techniques through descriptive analysis and multiple linear regression. The result of this research is that brand image partially affects customer satisfaction at PT. BNI (Persero) Tbk KCP Bayung Lencir, the product has no effect on customer satisfaction PT. BNI (Persero) Tbk KCP Bayung Lencir, service affects customer satisfaction PT. BNI (Persero) Tbk KCP Bayung Lencir and Promotion has no effect on customer satisfaction at PT. BNI (Persero) Tbk KCP Bayung Lencir. Meanwhile, brand image, products, services and promotions together have an effect on customer satisfaction at PT. BNI (Persero) Tbk KCP Bayung Lencir. The percentage of influence of brand image, products, services and promotions on customer satisfaction is 49.1%, while the rest is influenced by variables or other factors outside of this study.